2000
DOI: 10.1054/bjoc.2000.1506
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Fas ligand in normal and malignant breast epithelium does not induce apoptosis in Fas-sensitive cells

Abstract: Fas ligand (FasL) is expressed on some cancers and may play a role in the immune evasion of the tumour. We used immuno-histochemistry to study the expression of Fas and FasL in tissue samples from breast cancer patients, as well as normal breast tissue. Our results show that Fas and FasL are co-expressed both in normal tissue and in breast tumours. Fas and FasL mRNA were expressed in fresh normal and malignant breast tissue, as well as cultured breast epithelium and breast cancer cell lines. Flow cytometry ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Furthermore, FASL expression on breast tumor cells does not seem to cause apoptosis in neighboring lymphocytes. These results do not support an active role for FASL in the escape of breast tumors from immune attack [41]. In breast cancer development, transformed cells carrying the FASLÀ844 CC genotype that express high levels of FASL may create an immunoprivileged site by killing cytotoxic immune cells and thus escaping host immune-surveillance.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, FASL expression on breast tumor cells does not seem to cause apoptosis in neighboring lymphocytes. These results do not support an active role for FASL in the escape of breast tumors from immune attack [41]. In breast cancer development, transformed cells carrying the FASLÀ844 CC genotype that express high levels of FASL may create an immunoprivileged site by killing cytotoxic immune cells and thus escaping host immune-surveillance.…”
Section: Discussionmentioning
confidence: 66%
“…Extending that notion, in 1996 it was reported that human melanoma expressed FasL which was proposed to induce apoptotic death of antitumor T cells that enter the tumor parenchyma [38]. Additional papers supported that hypothesis [39,40], however, reagent and technical concerns were shown to underlie many conclusions [35] and in spite of demonstration of expression of FasL in some cancers [41], clinical disease progression does not correlate with FasL expression calling into question the physiological relevance of the notion [42]. The absence of solid evidence of apoptotic TIL in tumors and the ability to isolate viable TIL from a variety of tumor types also argues against the hypothesis [33].…”
Section: Are Til Killed Due To Fasl Expression By Tumor Cells?mentioning
confidence: 99%
“…T47D cells exhibit surface expression of both FasL and the Fas receptor, and stimulation with exogenous FasL leads to apoptosis (Keane et al, 1996;Ragnarsson et al, 2000). ZR-75-1 cells also undergo Fas-dependent cell killing when treated with the CH-11 activating antibody (Tong et al, 2001).…”
Section: Cell Surface Receptorsmentioning
confidence: 99%